Microscopical Characteristics, Phytochemical Screening and Antimicrobial Activity of Different Fractions of Litsea monopetala Leaves - Dam Ngoc Anh, Luu; Cong Hieu, Dinh; Khac Tiep, Nguyen; Thanh Tung, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2026)
Abstract: This study aimed to describe the microscopical characteristics, perform preliminary phytochemical analysis, and evaluate the antibacterial activity of different fractions of Litsea monopetala leaves. The leaves were collected from Pu Huong National Park and subjected to anatomical examination, phytochemical screening, fractionation, and in vitro antibacterial assays against methicillin-susceptible (MSSA) and methicillin-resistant (MRSA) Staphylococcus aureus . The results showed that the leaves exhibited distinct anatomical and powder features and contained at least six groups of organic compounds, including flavonoids and tannins. Antibacterial testing revealed that the ethyl acetate fraction exhibited the strongest activity, with a MIC of 1 mg/mL against both MSSA and MRSA, while the water and n -hexane fractions inhibited only MRSA at MIC = 4 mg/mL. These findings suggest that flavonoids and phenolic compounds in the ethyl acetate fraction are promising candidates for the development of anti- Staphylococcus aureus agents. Keywords: Litsea monopetala , leaf transverse section, thin-layer chromatography, flavonoids, Staphylococcus aureus , antimicrobial activity.